Customer loyalty in Sabah full-service restaurant - Phang Grace Ing; Ng, Zheng Lin; Ming Xu; Ramayah Thurasamy (Emerald Group Publishing Ltd., 2020)
Purpose – Loyal customers are committed to repeat patronage, make business referrals and provide publicity for the business. However, rising customer expectations and price consciousness, advancement of technology, lack of product differentiation and consumer choices have posted more challenges for customer retention. The purpose of this paper is to examine the relationships between transaction specific characteristics (i.e. food quality, service quality, atmosphere, convenience and price perception), customer satisfaction and customer loyalty (behavioral and attitudinal loyalties) in the context of Sabah full-service restaurant. The mediating effect of customer satisfaction and moderating effect of customer innovativeness were also tested. Design/methodology/approach – A total of 225 valid questionnaires was collected via purposive sampling method and analyzed using Smart-PLS software 3.0. Findings – All transaction specific characteristics have positive influences on customer satisfaction with price perception as the strongest predictor. Satisfaction had stronger effect on behavioral loyalty as compared to attitudinal loyalty. The mediating effects of customer satisfaction were only found in some of the relationships. None of the moderating effects of customer innovativeness was significant. Originality/value – Utilizing the value-percept theory and transaction specific model which combine the evaluations of service and product elements of the full-service restaurant, this study contributed to the better understanding of the relationships between transaction specific characteristics, customer satisfaction and customer loyalty. The examination of both attitudinal and behavioral loyalties provided valuable insights to practitioners and researchers in understanding full-service restaurant consumers’ repatronage intention, intention to spread positive words-of-mouth (WoM) and commitment.